Konflikt w Cabo Delgado i jego międzynarodowe implikacje w regionie Afryki wschodniej (Politeja, 2025)
CONFLICT IN CABO DELGADO AND ITS INTERNATIONAL IMPLICATIONS IN THE EAST AFRICA REGIONIn 2017, armed conflict erupted in Cabo Delgado, a northern province of Mozambique with a partly Islamic population. The militia of the organisation Ansar al-Sunna (also known as al-Shabab), which refers ideologically and programmatically to Muslim fundamentalism, launched armed operations against the institutions of the Mozambican state, aiming to introduce Sharia. The organisation’s terrorist modus operandi and widespread violence against civilians made this conflict part of the broader context of the expansion of jihadism in Africa. In 2018, the Islamic State announced the integration of local fundamentalist forces into the global network created by this terrorist structure. However, Ansar al-Sunna’s links with the Islamic State (IS) appear to be limited. The distance from IS’s decision-making centres and the limited possibilities for supply and personal contacts make it possible to view the conflict in Mozambique as peripheral from the point of view of IS’s main objectives, which of course does not mean ignoring its importance for regional stability. Local reasons for the outbreak of the conflict include the peripheral nature of Cabo Delgado province vis-à-vis the political centre, the lack of a developed social security infrastructure and, above all, the lack of significant progress in realising the expectations of the province’s inhabitants following the discovery of energy resources (in 2011-2012) on the continental shelf off the province’s coast. The threat of conflict spreading into Tanzanian territory threatened to internationalise the conflict. The Mozambican army’s lack of an effective strategy to eliminate terrorist threats necessitated the involvement of external actors to support its military efforts. At an initial stage, the authorities in Maputo engaged private actors offering military support (including the Wagner Group), but this was not successful. Subsequently, the international forces of the regional organisation SADC (SAMIM mission) and the Rwandan army became involved. The military action has helped to reduce the activity of jihadist forces, although Ansar al-Sunna guerrilla activity still poses a security threat in northern Mozambique.